Adequacy of Crop Residue Biomass as Renewable Energy Source for Tea Drying in Assam: A Spatial Assessment - Baruah, Devendra Chandra; Hiloidhari, Moonmoon (Journal of Agricultural Engineering, 2009)
Assam is the largest tea producing state with an annual contribution of about 51% of nation’s production. Coal, TD oil, and natural gas are used in tea drying as a source of thermal energy. Crop residue biomass is considered as a potential substitute of fossil energy. Availability of sufficient biomass in the vicinity of user location, avoiding costly transportation, is one of the major considerations. The present investigation makes a spatial analysis of paddy crop residue biomass availability vis-A-vis energy demand in tea drying in ten spatial units representing all the districts of Assam. Paddy is a major crop in Assam and grown in all the districts. Energy availability from paddy crop residue biomass was compared with the thermal energy demand for tea drying. Husk fuelled gasification and straw fired combustion technologies were considered with assumed levels of energy conversion efficiencies. The analysis indicated that tea drying in Assam required 12.43 PJ of thermal energy annually. Total annual available bio-energy was estimated as 5.09 PJ and 23.37 PJ from paddy husk and paddy straw, respectively. Overall, bio-energy availability from paddy husk would be sufficient to fulfil only 40.97% of the demand of the state. However, entire thermal energy demand for tea drying in Goalpara, Kamrup, Lakhimpur, Nagaon and Karbi-Anglong could be fulfilled through husk generated bio-energy in these districts. For the state as a whole as well as in seven spatial units (baring Dibrugarh, Sivasagar and North Cachar), bio-energy available from paddy straw would be adequate to fulfil the thermal energy demand for tea drying. Dibrugarh and Sivasagar were deficient in paddy residue biomass. An index is defined to test the adequacy of crop residue biomass to support energy demand in tea processing as ratio of growing areas of paddy and tea. The districts with ratio more than 3.58 were found to meet the resource adequacy criteria.